2011
DOI: 10.1111/j.1365-2672.2011.05102.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-locus variable-nucleotide tandem repeat subtype analysis implicates European starlings as biological vectors for Escherichia coli O157:H7 in Ohio, USA

Abstract: Aims:  To provide molecular epidemiological evidence of avian transmission of Escherichia coli O157:H7 between dairy farms in Ohio, this study was designed to identify genetic relatedness between isolates originating from bovine faecal samples and intestinal contents of European starlings captured on these farms. Methods and Results:  During a three‐year period (2007–2009), cattle (n = 9000) and starlings (n = 430) on 150 different dairy farms in northern Ohio were sampled for the presence of E. coli O157:H7. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 41 publications
5
34
0
Order By: Relevance
“…In conclusion, these data obtained from our laboratory‐based experiments are consistent with the epidemiological observations and ongoing research in our laboratory, supporting the role of European starlings in the epidemiology of E. coli O157 in livestock populations in the US (Wetzel and LeJeune 2006; Cerinicchiaro et al. 2011; Williams et al. 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, these data obtained from our laboratory‐based experiments are consistent with the epidemiological observations and ongoing research in our laboratory, supporting the role of European starlings in the epidemiology of E. coli O157 in livestock populations in the US (Wetzel and LeJeune 2006; Cerinicchiaro et al. 2011; Williams et al. 2011).…”
Section: Discussionsupporting
confidence: 89%
“…2006; Wetzel and LeJeune 2006). Our complementary studies have demonstrated an association between the number of starlings observed on dairy farms and the prevalence of E. coli O157 in milking cows (Cerinicchiaro et al 2011), and the isolation of indistinguishable molecular subtypes of E. coli O157 recovered from starlings and cattle (Williams et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by Williams et al (114), who reported that starlings and cattle on different farms had molecularly indistinguishable subtypes of STEC O157:H7, thus confirming that starlings were able to transmit STEC to different farms. Bolstering the role of starlings in STEC epidemiology is the fact that the number of starlings per milking dairy cow was also found to be significantly associated with the presence of STEC O157:H7 in bovine fecal pats (115).…”
Section: Birdsmentioning
confidence: 61%
“…For example, starlings have been implicated as biologic vectors in the dissemination of STEC among dairy farms in Ohio, United States ( 33 , 34 ), indicating that wildlife might play a key role in the epidemiology and ecology of STEC.…”
Section: Discussionmentioning
confidence: 99%